(3GdahGFO GdafGQjI Ydi GdQSGdI GdCKjQIs - (3GdafGQj (B( (3GdaQfj (B)(3, GdQhej, TeS GdOjf, eMeO Hf MeRI Hf eMeO, J (B834 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; MeOG dc Gddge Ydi eG dNUJ dj ef efM YhGQa GdCaGVd CeG HYO adeG de jfaYfj GdJYdd HYdd hYSi Yf GbJQGM CN dj aj cd UHGM heSG Cf CcJH ahGjO dGFbI HeWGdYI GdENhGf dahGjO GdQSGdI GdCKjQjI aj GdejRGf TQYJ ajgs
(3BNQgG (B:s
(3hGYde CfeG Ydjg GdGYJeGO hGdJYhjd ef gPg GdbjGSGJ EfeG gh GdHQgGf dchfg ehcHG Yf GdebOeGJ GdjbjfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 110s
(3eYLe GdeDdajf (B3 / 269s
(3cTa GdXfhf (B1 / 207s
(3TPQGJ GdPgH (B7 / 209s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs